Textual Notes on Sophocles, Ajax*. Issue 1 (1st January 2018) - Kraggerud, Egil; Welo, Eirik
Abstract : This article discusses some textual questions in Ajax leading to the following conclusions: I.54 add ⟨τ᾽⟩ after λείας. – II.208 the emendation ἠρεμίας ("rest", "quietude") suggested by Thiersch. – III.405a–b the proposal κράτη / μοι to fill the lacuna. – IV.476 defence of the line as transmitted. – V.546 τοσόνδε to go with ϕόνον. – VI.719 ἄνδρες, ϕίλον τι πρῶτον instead of ἄνδρες ϕίλοι, τὸ πρῶτον. – VII.869 instead of με write γε. – VIII.951 ⟨σὸν⟩ ἄχθος as a reference to Tecmessa's heavy burden of woe.